Confining Metal‐Organic Framework in the Pore of Covalent Organic Framework: A Microscale Z‐Scheme System for Boosting Photocatalytic Performance. Issue 7 (28th April 2022) - Deng, Yang; Wang, Yue; Di, Zichen; Xie, Mingsen; Dai, Fangfang; Zhan, Shaoqi; Zhang, Zhen
Abstract: The search for building hierarchical porous materials with accelerated photo‐induced electrons and charge‐carrier separation is important because they hold great promise for applications in various fields. Here, a facile strategy of confining metal‐organic framework (MOF) in the 1D channel of the 2D covalent organic framework (COF) to construct a novel COF@MOF micro/nanopore network is proposed. Specifically, a nitrogen‐riched COF (TTA‐BPDA‐COF) is chosen as the platform for in‐situ growth of a Co‐based MOF (ZIF‐L‐Co) to form a TTA‐BPDA‐COF@ZIF‐L‐Co hybrid material. The hierarchical porous structure endows TTA‐BPDA‐COF@ZIF‐L‐Co with superior adsorption capacity. In addition, the integration of TTA‐BPDA‐COF and ZIF‐L‐Co forms a Z‐scheme photocatalytic system, which significantly improved the redox properties and accelerated the separation of photogenerated charges and holes, achieving great improvement in photocatalytic activity. This confinement engineering strategy provides a new idea to construct a versatile molecular‐material photocatalytic platform. Abstract : Here, a facile strategy of confining a metal‐organic framework (ZIF‐L‐Co) in the 1D channel of a 2D covalent organic framework (TTA‐BPDA‐COF) to construct a novel TTA‐BPDA‐COF@ZIF‐L‐Co micro/nanopore photocatalyst is proposed. The integration of TTA‐BPDA‐COF and ZIF‐L‐Co forms a Z‐scheme photocatalytic system, which achieved great improvement in photocatalytic activity.